EVALUATION OF INPATIENT SATISFACTION WITH NURSING SERVICES AT PURUK CAHU REGIONAL GENERAL HOSPITAL - Dahliyana, Dahliyana; Tasalim, Rian; Wijaksono, Muhammad Arief; Basit, Muhammad (HEARTY, 2025)
Patient satisfaction is a critical indicator for assessing the quality of nursing services in hospitals, particularly in general surgery wards, where high-quality services can enhance recovery and reduce complications. In Indonesia, research on patient satisfaction in general surgery wards is limited, while patient visitation rates continue to rise annually. Therefore, understanding the factors influencing patient satisfaction is essential for improving nursing services. This study aims to evaluate the inpatient satisfaction levels with nursing services in the general surgery ward of Puruk Cahu Regional General Hospital. The research design is a descriptive quantitative study using a cross-sectional approach, involving all patients hospitalized in the general surgery ward during the study period. Data collection was conducted using a questionnaire adapted from the five Servqual dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The data analysis technique used is univariate descriptive to understand the distribution of patient satisfaction levels. The results show that the assurance and empathy dimensions have the highest satisfaction levels, while tangibles received the lowest scores, indicating a need for improvement in the hospital’s physical facilities. Overall, most patients are satisfied with the services provided, but there is still a need for improvements in certain aspects to enhance the patient experience. In conclusion, patient satisfaction with nursing services in the general surgery ward of Puruk Cahu Regional General Hospital is generally good, with a need for improvement in the tangibles and communication dimensions. These findings are expected to serve as a foundation for hospital management to enhance the quality of nursing services through facility improvements and enhanced communication skills of the nursing staff.